Analysis of Change Order Decision-Making Using The Analytic Network Process in The Operator Training Simulator Project at The Refinery Development Master Plan in The Oil And Gas Industry - Mahrtahmed Wira Panjijaya (Publikasi Indonesia, 2025)
The Refinery Development Master Plan (RDMP) project at PT X aims to increase the capacity and efficiency of the refinery. A key aspect of this Residue Fluid Catalytic Cracking (RFCC) unit project is the development of an Operator Training Simulator (OTS) to ensure practical operator training. However, the change order decision-making process associated with developing the OTS is often complex and influenced by various factors. This research uses a Decision Support System by combining a Delphi - DEMATEL-based approach with Analytic Network Process (ANP) techniques to analyze the change order decision-making process. The Delphi method gathers expert opinions and identifies key factors that influence the decision-making process, and the DEMATEL method is used to see the interrelationships between criteria. Meanwhile, the ANP method structures and prioritizes these factors. The results of this study provide a structured framework for decision-making in the OTS development change order process that managers and stakeholders can use to ensure effective and efficient decision-making.